Academic Senate Minutes 2008-02-21 - Academic Senate:::::::::
Chair Report. Minutes of 10/25; 11/8; 11/29; 12/13 and 2/7/08 – Approved. Agenda approved. Geography/Global Studies revision – approved. Request for endorsement of SSU production of the Vagina Monologues – Endorsed. Associated Student Report. Chair-Elect report. Vice President of Administration and Finance Report. EPC report (GE assessment). RTP revision – First Reading Completed. University 150 (FYE) – First Reading Completed. Ad-Hoc Remedies on Response to the Vote of No Confidence – First Reading Completed. Sustainability Resolution Approved. Update on WASC. Questions for the President.